IMAGE ENHANCEMENT USING CONTRAST STRETCHING ON RGB AND IHS DIGITAL IMAGE - Kartika Firdausy; Tole Sutikno; Eko Prasetyo (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2007)
Low contrast image has relatively bad quality since its information can not be directly interpreted by human eyes. It’s quality can be improved using contrast stretching operation. The objective of this paper is to design software for enhancement using contrast stretching on RGB and IHS digital image models. The operation is a point operation, that each pixel on the image is processed individually, by darkening dark pixels and brightening bright pixels. The development of the software was done using TBitmap class in Borland Delphi 6.0. Tests have been performed on BMP and PEG grayscale as well as color images. The test result shows that the developed software is capable to enhance the contrast of the sample images, which are shown by the expansion of the histograms of the images.